Meningkatkan Hasil Belajar Bahasa Indonesia pada Aspek Membaca dengan Materi Pokok Membaca Teks Cerita Pendek Melalui Penerapan Metode Resitasi - Satriya Nugroho, R. Adi (Journal of Education Action Research, 2018)
The purpose of this study is to improve the learning outcomes of Indonesian language with the material of reading short story texts through the application of recitation learning methods in learning Indonesian in class XI of the First Semester of SMK Negeri 60 Jakarta. The research method used is descriptive, the type of research is class action. The research subjects were 34 grade XI students of SMK Negeri 60 Jakarta. The technique used is direct observation. Data collection tools are teacher and student observation sheets. This research was carried out through two cycles, the research procedure using the stages of planning, implementation, observation and reflection. Classroom Action Research Results on Indonesian language subjects about reading short story texts through the application of the Recitation method are: learning outcomes in the first cycle the average value shows 78.20, while the learning outcomes in the second cycle the average value shows 83.41. Based on the results of the study it can be concluded that by applying the recitation method in learning Indonesian language can improve the learning outcomes of Indonesian with the main material of reading short story texts for class XI students of SMK Negeri 60 Jakarta successfully.